SEMANTIC ANALYSIS OF A MARK FROM A CONSERVATED LIBRARY CABINET OF THE SECOND HALF OF THE ХІХ CENTURY OF LVIV POLYTECHNIC NATIONAL UNIVERSITY - Чорний , Максим (Art and Design, 2024)
The purpose of the article is to determine the origin, semantic meaning, and reasons for the presence of specific community symbols on the example of an object undergoing a series of conservation measures. Methodology. In order to achieve this goal, the method of visual, historiographical, stylistic analysis, as well as the methods of generalization, interpretation, abstraction and description of the studied gem from the library cabinet of the main building of the Lviv Polytechnic National University as part of a preliminary conservation study were used. Results. Having studied the coat of arms decorating the supporting columns of the gallery of the library cabinet, we have identified its main compositional forms and constituent elements, namely: cartouche, oval background, and its emblem as the most expressive feature. After analyzing the main features of the use of such emblems in the heraldry of noble families, craftsmen, merchants and bourgeois, their common characteristics and semiotic load, it was found that the emblem from the coat of arms of the cabinet is a merchant’s mark. Having established the authorship and history of the Library Cabinet from the main building of the Lviv Polytechnic National University, the author hypothesizes that the mark-monogram was formed from the initial letters of the names of Julian Zachariewicz and the sculptor Leonard Marconi, respectively: J - Julian and L - Leonard. The scientific novelty of the article is to establish the hitherto unknown content of the decorative decoration in the wooden sculpture of the library cabinet of the second half of the nineteenth century of the main building of the Lviv Polytechnic National University. The practical significance is to expand the understanding of the semantic features and the historical and cultural context that exists during the creation of works of decorative and applied arts and crafts, as well as to establish the fact of a close relationship between the authors and their creations on the example of the Lviv architectural and artistic center in the second half of the nineteenth century. The results of the study can be used in the field of art history, design, as well as in the development of conservation programs and research.